Modified Gegen Qinlian Decoction modulated the gut microbiome and bile acid metabolism and restored the function of goblet cells in a mouse model of ulcerative colitis - Huang, Jinke; Zhang, Jiaqi; Wang, Fengyun; Tang, Xudong (Frontiers in Immunology, 2024)
Objective Modified Gegen Qinlian Decoction (MGQD) has been shown to effectively relieve ulcerative colitis (UC) without a known pharmacological mechanism. In this study, the anti-colitis efficaciousness of MGQD and its underlying mechanisms in UC were evaluated. Methods Mice with colitis were administered MGQD for 7 days. Following the evaluation of clinical symptoms, gut microbiota in the feces of UC mice was examined using 16S rRNA sequencing and bile acids (BAs) were examined using LC/MS. Gut microbiota consumption and fecal microbiota transplantation (FMT) were used to explore the involvement of gut microbiota in the anti-UC action of MGQD. Results MGQD relieved colitis as shown by weight loss protection, a lower disease activity index (DAI), restoration of intestinal length reduction, and lower histopathologic scores. MGQD also restored crypt stem cell proliferation and function of colonic goblet cells, and promoted MUC2 protein secretion. Interestingly, investigations using gut bacterial depletion and FMT showed that MGQD attenuated colonic damage in a gut-dependent way. The modulation of the gut microbiota by MGQD might be attributed to a decrease in Odoribacter and an increase in norank_f_Muribaculaceae. In addition, MGQD modulated the metabolism of BAs while restoring the structure of the gut microbiota. Conclusion MGQD significantly alleviated colitis in mice, which may be associated with the modulation of gut microbiota and BA metabolism and restoration of function of goblet cells. However, factors other than the gut microbiota may also be involved in the amelioration of UC by MGQD.